Influence of crystal structural orientation on impedance and piezoelectric properties of KNN ceramic prepared using sol-gel method - I. Izzuddin,; M.H.H. Jumali,; Z. Zalita,; J.N. Huwaida,; R. Awang, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this study was to investigate the effect of structural orientation on the impedance and piezoelectric properties of Ka0.5Na0.5NbO3 (KNN) ceramic synthesized using modified sol-gel method. Dried xerogel was heated at 800oC for 90 min and the aggregates were grinded to powder form. SEM micrographs confirmed that the powder consist of bimodal particles in nm and μm size regimes. The powder was compacted into 13 mm diameter pellet and sintered at 1000oC for 6 h. Then the pellets were poled at 4.0kV/mm at 100oC for 30 min. The as-sintered pellets displayed different sizes of cuboidal granules forming a relatively dense sample. The XRD and Raman spectroscopy results confirmed the formation of perovskite KNN with monoclinic crystal structure. The compositional analysis using Vegard’s law showed that the K:Na ratio was 0.5:0.5. Dramatic intensity enhancement in (110) reflection and subsequent reduction in (100) reflection as observed in X-ray diffractograms for the poled pellet suggest permanent shift in crystal orientation. Consequently, the Nyquist impedance plot of a Debye type semicircular arc was altered to a combination of a depressed semicircular arc. Unlike the initial plot, the real impedance, Z′ exhibited frequency dependence at low frequency regime. In addition, the relaxation time, τ of KNN sample shifted to lower frequency after the structural re-orientation while piezoelectric constant, d33 along (110) direction significantly improved from 5 to 35 pC/N.